2020
DOI: 10.1007/s00262-020-02749-8
|View full text |Cite|
|
Sign up to set email alerts
|

IL-15 superagonist N-803 improves IFNγ production and killing of leukemia and ovarian cancer cells by CD34+ progenitor-derived NK cells

Abstract: Allogeneic natural killer (NK) cell transfer is a potential immunotherapy to eliminate and control cancer. A promising source are CD34 + hematopoietic progenitor cells (HPCs), since large numbers of cytotoxic NK cells can be generated. Effective boosting of NK cell function can be achieved by interleukin (IL)-15. However, its in vivo half-life is short and potent trans-presentation by IL-15 receptor α (IL-15Rα) is absent. Therefore, ImmunityBio developed IL-15 superagonist N-803, which combines IL-15 with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 46 publications
(102 reference statements)
1
31
1
2
Order By: Relevance
“…Another explanation might be that our HPC-NK cells are already highly activated in the presence of OC cells without gemcitabine treatment (Figure 4). 6,16,[24][25][26][27][28] In previous publications, we have shown that we can already approach nearly 100% HPC-NK cell-mediated OC cell death in the absence of gemcitabine using an E:T ratio of 10:1, which is lower compared to the E:T ratio that is needed for peripheral blood (PB)-NK cells to kill 100% of OC cells. 6,16 However, to study possible additive effects of HPC-NK cells and gemcitabine in a more physiological setting, all combination experiments were performed at low E:T ratios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation might be that our HPC-NK cells are already highly activated in the presence of OC cells without gemcitabine treatment (Figure 4). 6,16,[24][25][26][27][28] In previous publications, we have shown that we can already approach nearly 100% HPC-NK cell-mediated OC cell death in the absence of gemcitabine using an E:T ratio of 10:1, which is lower compared to the E:T ratio that is needed for peripheral blood (PB)-NK cells to kill 100% of OC cells. 6,16 However, to study possible additive effects of HPC-NK cells and gemcitabine in a more physiological setting, all combination experiments were performed at low E:T ratios.…”
Section: Discussionmentioning
confidence: 99%
“…CD34 + HPCs were expanded and differentiated into HPC-NK cells within 5-6 weeks as described previously. 16 HPC-NK cells (>70% CD56 + ) were used directly after culture or after cryopreservation and 5-8-day re-culture. HPC-NK cells were cultured in Iscove's Modified Dulbecco's Medium (IMDM, Gibco, 21980-032) supplemented with 10% fetal calf serum (FCS, Corning, 35-079-CV or Integro, 5-45900) (IMDM10; HPC-NK cell functional assay) or Roswell Park Memorial Institute 1640 medium (RPMI, Gibco, 21875-034) with 10% FCS (RPMI10; phenotyping and killing assay).…”
Section: Hpc-nk Cell Culturementioning
confidence: 99%
“…Other approaches consist of coupling IL-15 to the sushi domain of the IL-15Rα that is fused to and IgG-Fc fragment antibodies to increase its stability. The IL-15 supplementation to NK cells using this molecule, ALT-803, demonstrated improved anti-tumor outcomes in preclinical models [284][285][286][287][288] and phase I clinical trials [289]. Given these promising results, such treatments are currently being tested in HCC, aiming to reverse NK cell dysfunction and enhance patient outcomes (Table 3).…”
Section: Therapeutic Interventionmentioning
confidence: 99%
“…С худшим прогнозом при РЯ коррелирует накопление CD33 + миелоидных супрессорных клеток в БС (под влиянием VEGF), которое ведет к неспособности накапливать CD8 + клетки [49]. Злокачественные новообразования чувствительны к иммунитету, опосредованному натуральными киллерами (NK) [50]. В экспериментах in vivo на модели ксенотрансплантата мыши показана эффективность высокоактивных NK, полученных из человеческих CD34 + гемопоэтических стволовых и прогениторных клеток, в инфильтрации и опосредованном уничтожении сфероидов РЯ [51].…”
Section: обзор литературыunclassified
“…Большое количество цитостатических NK может быть получено из различных источников, включая пуповинную кровь. Терапия при помощи NK является перспективной стратегией в лечении рака, так как позволяет избирательно воздействовать на раковые клетки без нанесения вреда здоровым тканям [50]. Данные механизмы активно изучаются.…”
Section: перспективы исследований большого сальника для терапии рака unclassified